Peningkatan Kapasitas Kepala Desa Dan Aparatur Desa (Studi Terhadap Penyusunan Perencanaan Pembangunan Desa Dalam Pengelolaan Dana Desa Indralaya Selatan Kabupaten Ogan Ilir) - Mietha Nella (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The aim of this research is to determine the capacity building of village heads and village officials (study of the preparation of village development planning in managing village funds in South Indralaya, Ogan Ilir Regency). The capacity of the Village Head and South Indralaya Village Apparatus, Ogan Ilir Regency is seen from three indicators, namely, understanding, skills and abilities. The type of research used was descriptive using a qualitative approach. There were 11 research informants with 1 person as the key informant. Data collection techniques used interview techniques (based on interview guidelines), observation and documentation. Next, data analysis was carried out qualitatively. The results of this research show that at the level of understanding, the South Indralaya Village Apparatus already understands the preparation of village development planning. In terms of skills indicators, the South Indralaya Village Apparatus has carried out its duties and functions skillfully. In terms of capacity indicators, the South Indralaya Village Apparatus has been able to prepare village development plans in accordance with community expectations and is able to manage village funds in accordance with provisions. This shows that there has been an increase in the capacity of the South Indralaya Village Apparatus, Ogan Ilir Regency compared to the previous year. The South Indralaya Village Apparatus, Ogan Ilir Regency has been provided with training and education that supports capacity increase.